2013
DOI: 10.1248/bpb.b12-00627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyphenols on Production of Steroid Hormones from Human Adrenocortical NCI-H295R Cells

Abstract: Modulating steroid hormone levels is a curative and preventive measure for Cushing's syndrome, aldosteronism, and various stress-triggered symptoms. Polyphenols have been reported to inhibit steroidogenic enzymes such as 3β-hydroxysteroid dehydrogenase (3β-HSD) and aromatase. However, evidence for their inhibitory effects is fragmentary because it has been determined in studies with small groups of steroid hormones. To investigate the effects of steroids on complete steroidogenic pathways, comprehensive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…In our study, intraperitoneal administration of apigenin in mice affected the classical and alternative pathways of bile acid metabolism by increasing chenodeoxycholic acid, lithocholic acid, taurohyodeoxycholicacid, hyodeoxycholic acid, and cholesterol derivatives. Apigenin was shown to significantly down‐regulate the expression of 3β‐HSD (3β‐hydroxysteroid dehydrogenase), CYP17A1 (17α‐hydroxylase), and CYP21A2 (21‐hydroxylase) at mRNA levels (Hasegawa et al, ). 3β‐HSD is an enzyme that catalyzes the biosynthesis of progesterone from pregnenolone, 17α‐hydroxyprogesterone from 17α‐hydroxypregnenolone, and androstenedione from dehydroepiandrosterone (DHEA) in the adrenal gland (Lachance et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, intraperitoneal administration of apigenin in mice affected the classical and alternative pathways of bile acid metabolism by increasing chenodeoxycholic acid, lithocholic acid, taurohyodeoxycholicacid, hyodeoxycholic acid, and cholesterol derivatives. Apigenin was shown to significantly down‐regulate the expression of 3β‐HSD (3β‐hydroxysteroid dehydrogenase), CYP17A1 (17α‐hydroxylase), and CYP21A2 (21‐hydroxylase) at mRNA levels (Hasegawa et al, ). 3β‐HSD is an enzyme that catalyzes the biosynthesis of progesterone from pregnenolone, 17α‐hydroxyprogesterone from 17α‐hydroxypregnenolone, and androstenedione from dehydroepiandrosterone (DHEA) in the adrenal gland (Lachance et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have also been shown to modulate key enzymes in adrenal steroidogenesis, affecting steroid hormone biosynthesis in the mineralocorticoid, glucocorticoid, and adrenal androgen pathways (Schloms & Swart, 2014). The estrogenic properties of apigenin have already been described (Hasegawa, Nakagawa, Sato, Tachikawa, & Yamato, 2013). Apigenin is able to trigger steroidogenic acute regulatory (StAR) gene expression at the transcriptional level and steroid hormone production in mouse Leydig cells by blocking the thromboxane A2 receptor and reducing the DAX-1 (dosage sensitive sex reversal-adrenal hypoplasia congenita critical region on the X chromosome, gene-1) protein, a transcriptional repressor of StAR gene expression (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Liquid Cromatography-Tandem Mass Spectrometry. Steroid extraction was performed as described in [19] and is reported in the Supplementary Materials and Methods. Analysis was carried out using a highperformance liquid chromatography (HPLC) system (1260 Series Agilent Technologies; Santa Clara, CA, USA) equipped with a reversed-phase Hypersil Gold C8 (100 x 3mm 3um) analytical column (Thermo AA was administered i.p (196 mg/Kg) daily for 16 days (qdx16); control mice received the vehicle (2.5%benzyl alcohl, 97.5% safflower oil).…”
Section: Quantitative Rt-pcr (Qrt-pcr) Gene Expression Was Evaluatedmentioning
confidence: 99%
“…It has been reported that certain polyphenols inhibit digestive enzymes such as lipase, α-amylase, α-glucosidase, 6) and steroidogenic enzymes, 7) as well as liver microsomal glucuronidation of estrone and estradiol.…”
Section: Effect Of Polyphenols On Hmg-coa Lyase Activitymentioning
confidence: 99%
“…5,6) We recently reported that apigenin, a flavonoid found in several herbs including parsley, thyme, and peppermint, inhibits steroidogenic enzymes of cytochrome P450 (CYP)17 and CYP21, as well as 3β-hydroxysteroid dehydrogenase. 7) HMG-CoA lyase in hepatic cells is a rate-limiting enzyme catalyzing the cleavage of HMG-CoA to acetoacetate, and thus inhibition of this enzyme results in reduced acetoacetate production, in other words, impaired ketogenesis. Based on the notion that inhibition of HMG-CoA lyase possibly prevents ketoacidosis and the identification of therapeutic targets, we examined the inhibitory effects of polyphenols on HMG-CoA lyase activity in cellular extracts of human hepatoma HepG2 cells.…”
mentioning
confidence: 99%